2015
DOI: 10.1007/s00221-015-4344-3
|View full text |Cite
|
Sign up to set email alerts
|

Temporal changes of light-induced proteins in the SCN following treatment with the serotonin mixed agonist/antagonist BMY7378

Abstract: The 5-HT1A mixed agonist/antagonist BMY7378 has been shown to greatly potentiate photic phase advances in hamsters. The underlying mechanism and intracellular changes in the suprachiasmatic nucleus (SCN) by which this potentiation is accomplished have yet to be fully determined. Here, we examine the effect of BMY7378 on temporal activation patterns of a number of proteins and enzymes in the SCN following light exposure in the late subjective night. BMY7378 administration increased the amount of several photo-i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 39 publications
1
6
0
Order By: Relevance
“…As readouts for a functional circadian system, rhythms in spontaneous locomotor activity and serum corticosterone levels were determined before and after therapeutic irradiation. In addition, p‐ERK immunohistochemistry was used as a marker for rhythmic SCN neuronal activity under light/dark conditions 28‐30 …”
Section: Discussionmentioning
confidence: 99%
“…As readouts for a functional circadian system, rhythms in spontaneous locomotor activity and serum corticosterone levels were determined before and after therapeutic irradiation. In addition, p‐ERK immunohistochemistry was used as a marker for rhythmic SCN neuronal activity under light/dark conditions 28‐30 …”
Section: Discussionmentioning
confidence: 99%
“…The 5‐HT 1A receptor mixed agonist/antagonist 8‐[2‐[4‐ (2‐Methoxyphenyl)‐1‐piperazinyl] ethyl]‐8‐azaspiro [4.5] decane‐7, 9‐dione dihydrochloride (BMY7378, Sigma Aldrich, Oakville, ON, USA) was dissolved in physiological saline and administered through osmotic mini pumps. Previously, we had examined the acute effects of this drug (Smith et al ., ,c) at a dose of 5 mg/kg. Here, we elected to use this same dose but spread over the full 24 h day (i.e., 5 mg/kg/day).…”
Section: Methodsmentioning
confidence: 99%
“…The 5‐HT 1A receptor is required for this potentiation (Smith et al ., ). In the SCN, light‐induced expression of c‐Fos, JunB, and PER1 (Recio et al ., ; Smith et al ., , ) and phosphorylation of cAMP response element‐binding protein (Smith et al ., ) are altered by NAN‐190 or BMY7378 pre‐treatment. It has been suggested that systemic administration of these drugs might enhance circadian responses to light by decreasing 5‐HT release from the raphe, while simultaneously disinhibiting the retinal terminals in the SCN, leading to greater neurotransmitter release following a light pulse (Gannon, ).…”
Section: Introductionmentioning
confidence: 97%
“…These drugs bind to the 5-HT 1A receptor and are thought to act as agonists at raphe autoreceptors and as antagonists at post-synaptic receptors (Rydelek-Fitzgerald et al, 1990;Claustre et al, 1991;Gannon, 2003). When these drugs are given prior to a light pulse the resulting phase advances can be up to 250% greater than to light alone (Rea et al, 1995;Moriya et al, 1998;Takahashi et al, 2002;Gannon, 2003;Gannon & Millan, 2006;Sterniczuk et al, 2008;Smith et al, 2010Smith et al, , 2015b. Interestingly, both BMY7378 and have been shown to enhance photic shifts when administered even up to 6 h after a light pulse (Kessler et al, 2008;Lungwitz & Gannon, 2009).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation